Epidemiological and Clinical Characteristics of Melioidosis Caused by Gentamicin-Susceptible Burkholderia pseudomallei in Sarawak, Malaysia - Sia, Tonnii LL; Anand, Mohan; Ooi, Mong-How; Chien, Su-Lin; Tan, Lee-See; Goh, Charles; Pang, Daniel C. L.; Bart J., Currie; Wong, Jin-Shyan; Yuwana, Podin (Oxford University Press, 2021)
Burkholderia pseudomallei, the causative agent of melioidosis, is intrinsically resistant to a broad range of antibiotics, including aminoglycosides. In Sarawak, Malaysia, a high proportion of melioidosis cases are caused by gentamicin-susceptible isolates. There are limited epidemiological and clinical data on these infections. Methods. We conducted a retrospective study of culture-confirmed melioidosis among adults admitted to Bintulu Hospital in Sarawak, Malaysia, from January 2011 until December 2016.